Toxic epidermal necrolysis treated with filgrastim and dexamethasone - Choudhary, Nishant; Sharma, Nidhi; Sinha, Sujata; Das, Sudip (International Journal of Research in Dermatology, 2019)
We report a case of 22 year female with toxic epidermal necrolysis while on carbamazepine. One hospital outside treated her with steroids but she didn’t show any improvement and rather worsened. The patient reported to us with fluctuating blood pressure and dyselectrolytemia. Patient also developed neutropenia (3,200/mm3) and sepsis. Patient was treated with filgrastim and dexamethasone. Filgrastim was added because of neutropenia and earlier case reports suggesting it aid in faster healing. Patient made a complete recovery.